Betrayed as boys psychodynamic treatment of sexually abused men - Gartner, Richard B. (Guilford Press, 1999)
"More than one in six boys in the United States are sexually victimized by the age of sixteen. This much-needed volume examines how sexual betrayal affects boys and the ways they carry this hurt into adulthood. Blending psychoanalytic understanding with insights from trauma-oriented theory and practice. Richard B. Gartner presents effective strategies for meeting the unique therapeutic needs of men with sexual abuse histories. Filled with evocative clinical material, the book draws readers into the direct experience of these clients, the therapists who work with them, and the constantly shifting relational world they inhabit. It provides an indispensable map and guide for clinicians and educators in a range of settings."--BOOK JACKET.